Pengaruh program literasi dan numerasi terhadap motivasi belajar siswa sekolah dasar: studi kuantitatif asosiatif di SD Negeri Deresan - Arief, Ardian; Lalita, Dohitra Avril; Setyawan, Arya Dani; Taryatman, Taryatman (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This study aims to analyze the influence of literacy and numeracy programs on the learning motivation of elementary school students. The approach used is associative quantitative with multiple linear regression analysis. The research population included all 57 students in grade V of SD Negeri Deresan, with a sample of 56 students. The research instrument is a questionnaire with a Likert scale that has been validated and reliable. The results showed that the literacy program had a significant effect on students' learning motivation (sig = 0.000 < 0.05) and the numeracy program also had a significant effect (sig = 0.004 < 0.05). Simultaneously, the two programs contributed 53.2% to the increase in learning motivation (Adjusted R² = 0.532). These findings indicate that the implementation of literacy and numeracy programs can meaningfully increase the learning motivation of elementary school students.